Record of melanism in Tamandua tetradactyla (Pilosa: Myrmecophagidae) in Perú - Portillo, Alejandro (2022)
A case of melanism in Tamandua tetradactyla (Myrmecophagidae) is recorded, based on an individual observed in the Huánuco Department, Peru. Two previous records are found in the iNaturalist database. With this record, the number of melanistic mammal species in Peru increases to four. It should be noted that cases of melanism in this species have already been reported in the Neotropics.